Effects of Recombinant Human Lactoferrin on Osteoblast Growth and Bone Status in Piglets. Issue 2 (3rd April 2018) - Li, Qiuling; Zhao, Jie; Hu, Wenping; Wang, Jianwu; Yu, Tian; Dai, Yunping; Li, Ning
ABSTRACT: Lactoferrin (LF), an ~80 kDa iron-binding glycoprotein, modulates many biological effects, including antimicrobial and immunomodulatory activities. Recently, it was shown that LF also regulates bone cell activity, suggesting its therapeutic effect on postmenopausal bone loss. However, a minimal amount is known regarding the effects of recombinant human LF (rhLF) supplementation on bone status in young healthy infants. We found osteoblast cell differentiation was significantly promoted in vitro . Furthermore, treatment of human osteoblast cells with rhLF rapidly induced phosphorylation of p44/p42 mitogen-activated protein kinase (p44/p42 MAPK, ERK1/2). In order to investigate the effects of rhLF on bone status in vivo, we used a piglet model, which is a useful model for human infants. Piglets were supplemented with rhLF milk for 30 days. Bone formation markers, Serum calcium concentration, bone mineral density (BMD), bone mineral content (BMC), tibia bone strength, and the overall metabolite profile analysis showed that rhLF was advantageous to the bone growth in piglets. These findings suggest that rhLF supplementation benefits neonate bone health by modulating bone formation.